The Assessment of Physiotherapy Practice tool provides informative assessments of clinical and professional dimensions of student performance in undergraduate placements: a longitudinal validity and reliability study - Reubenson, Alan; Ng, Leo; Gucciardi, Daniel (AUSTRALIAN PHYSIOTHERAPY ASSOC, 2020)
© 2020 Australian Physiotherapy Association